Notre Dame’s wooden beams: reflections on restoration, forestry education, and EU Directives - Romagnoli M; Agrimi M; Togni M (Forest@)
The recent restoration of Notre Dame Cathedral’s “Forest of Wooden Beams” exemplifies the enduring relevance of traditional construction methods and forest science in contemporary architecture. This monumental project, recently completed, utilized about 2,400 carefully selected oak beams, showcasing centuries-old French forestry practices rooted in meticulous silviculture. These practices, dating back to Colbert (1619-1683), produce high-quality timber with fine texture and uniform growth patterns, meeting today’s stringent structural standards. In light of recent European regulations, solid wood in construction has gained new importance, with Harvested Wood Products (HWPs) playing a crucial role in climate change mitigation. This intersection of traditional silvicultural practices and environmental concerns highlights forestry’s evolving role in sustainable development. Forestry and Environmental Sciences graduates are well-equipped to address these challenges, but require supportive policies to fully utilize their skills. The Notre Dame restoration underscores the need to adapt forest science education to meet contemporary sustainability challenges. By combining historical knowledge with modern scientific understanding, we can ensure the continued relevance of forest management and pave the way for innovative approaches to construction and environmental stewardship.